PENGARUH KOMPENSASI DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN DI PERUSAHAAN DAERAH AIR MINUM (PDAM) WAY RILAU BANDAR LAMPUNG - Febrian Eko Saputra; Muhammad Anton Ferdiansah; Defia Riski Anggarini (TECHNOBIZ : International Journal of Business, 2025)
This study aims to evaluate the impact of compensation and work motivation on improving employee performance at the Regional Drinking Water Company (PDAM) Way Rilau. A quantitative approach was used, with a population consisting of employees at PDAM Way Rilau in Bandar Lampung. The sample was selected using purposive sampling within non-probability sampling. According to Artikunto, if the number of individuals is less than 100, it is advisable to include all of them. However, for larger populations, a sample of around 10% or more can be taken. In this study, the sample size was 26 respondents. Data was collected through a survey using a questionnaire. Data analysis was performed using multiple linear regression. Using the SPSS application, the research results indicate that both compensation and motivation have a positive and significant effect on employee performance at PDAM Way Rilau Bandar Lampung. These findings are expected to assist the company in enhancing employee performance through improvements in the compensation system and motivation strategies